Honey improves lipid profile of diet-induced hypercholesterolemic rats - Titis Nurmasitoh; Miranti Dewi Pramaningtyas (Universa Medicina, 2016)
Background Coronary heart disease (CHD) is a major cause of morbidity and mortality throughout the world, including Indonesia. One of the risk factors for CHD is hypercholesterolemia. One of the natural products that has been developed for the treatment of hypercholesterolemia is honey. Honey contains fructooligosaccharides, various vitamins, minerals, and enzymes which are supposedly able to lower blood cholesterol levels. This research aimed to study the influence of honey on the levels of blood total cholesterol, triglyceride, and low density lipoprotein (LDL) levels in Wistar rats.